The Arts Interview. Conrad Furey : Resettlement - Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland. Division of Educational Technology, 1985)
Host Fred Hollingshurst interviews Newfoundland-born painter and sculptor Conrad Furey whose works largely reflect Newfoundland themes such as resettlement, although he has relocated to Ontario. Furey discusses his current exhibition as well as and his artistic style. Examples of his works are included. Thanks to the MUN Art Gallery. Produced by Memorial University Television. Technical credits at end.